American terrorist : Timothy McVeigh & the Oklahoma City bombing - Michel, Lou, 1955-; Herbeck, Dan. (New York : Regan Books, 2001)
At 9:02 A.M. on April 19, 1995, in the largest terrorist act ever perpetrated on American soil, the Alfred P. Murrah Federal Office Building in Oklahoma City was destroyed by the explosion of a homemade truck bomb. One hundred and sixty-eight people, including nineteen children, were killed by the blast and more than five hundred others were injured. Timothy J. McVeigh, an antigovernment activist, was tried and convicted of the bombing. But to Americans everywhere, the story has remained a mystery, held hostage by McVeigh's refusal to explain or even discuss the event and his involvement. With this book, that mystery is solved and it will change our understanding of the crime. The authors have been researching the Oklahoma City bombing and the life of Tim McVeigh since the week the tragedy occurred. They have interviewed more than one hundred and fifty people from every stage of McVeigh's life, from his childhood friends to the psychiatrist hired by the defense team to examine him before his trial. They have garnered the cooperation of McVeigh's father, mother, and sister Jennifer, and gained exclusive access to previously unpublished family photographs and personal effects. In April 1952 during more than seventy-five hours of interviews, they persuaded Timothy McVeigh to give the first complete, candid, no-holds-barred account of his story, an account given with no compensation or right of approval, that sheds light on every aspect of McVeigh's life. It describes his relationship with Terry Nichols and Michael Fortier and the consuming distrust of the government shared by the three. And in its pages every detail of the bombing itself is reconstructed, from the origins of the plot to the moment of detonation and McVeigh's aborted getaway. This book puts to rest conspiracy theories that have previously gone unresolved. It clarifies the role and responsibility of every person who has been implicated in the plan. And it explains, thoroughly and definitively, how a decorated war hero from rural New York State became the worst mass murderer in the nation's history.
Acknowledgments -- Introduction -- Part I. Growing up. 1. The boy next door -- 2. Real world -- 3. A hundred Tim McVeighs -- 4. War hero -- Part II. 5. Nothingness -- 6. Kindred spirits -- 7. Won't be back forever -- 8. Ready to kill -- Part III. Bomber. 9. Ground zero -- 10. Body count -- 11. Timmy's all over CNN -- 12. Indicted -- Part IV. Infamy. 13. Oh, my God, he did it -- 14. Murderer's row -- Dusk. Appendix A -- Appendix B -- Source notes -- Index.
Includes index.
Keywords: McVeigh, Timothy; Terrorists -- United States -- Biography; Right-wing extremists -- United States -- Biography; Oklahoma City Federal Building Bombing, Oklahoma City, Okla., 1995.